Law Enforcement Against the Criminal Act of Human Trafficking with the Purpose of Labor Exploitation - Ferdiansyah Ferdiansyah; Timbul Dompak (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
The practice of labor exploitation is not new. Labor exploitation has been widespread since the colonial era. Some people use print media, social media, and even word-of-mouth to market. Although this is nothing new, labor exploitation is still happening and is growing more concerning. Due to the fact that it involves both domestic and international offenders, this is the case. between nations. The methods used in human trafficking crimes have become more complex as communication, information technology, and transformation have advanced. The criminals are looking for victims from the lower social classes. It is not unusual for offenders to help victims by giving them debt or company cash. Some even go so far as to give scholarships to those who want to pursue further education overseas. According to the Witness and Victim Protection Agency (LPSK), which has verified this, human trafficking, particularly labor exploitation, does not discriminate. Because human trafficking, particularly labor exploitation, disregards age and gender. age and gender. Labor exploitation affects both men and women, as well as children and adults. Law No. 21/2007 on the Eradication of the Crime of Trafficking in Humans, Law No. 18/2017 on the Protection of Workers, and Law no. 18/2017 on the Protection of Migrant Workers all prohibits the trafficking of humans for the purpose of labor exploitation. Workers who are migrants. This paper addresses several topics, including the criminal law's prohibitions against trafficking in persons for the purpose of labor exploitation, the need for immediate enforcement of these prohibitions, and the elements that contribute to trafficking in persons for the purpose of labor exploitation. labor exploitation, as well as elements that contribute to human trafficking for the prevalence of labor exploitation is increasing. Labor exploitation is becoming more and more common. The descriptive analytical method was employed in the study. method of analytical descriptive research. It is anticipated that this research will offer a complete, methodical, and exhaustive analysis.